ANALISIS INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN TUTORIAL TATAP MUKA DI UPBJJ-UT BENGKULU - Dwi Kristanti (LPPM Universitas Terbuka, 2019)
Public services by the government in various sectors are sometimes perceived as not in line with public expectations. The purpose of this study was to analyze the quality of face-to-face tutorial services at Universitas Terbuka (UT) Regional Office in Bengkulu, using the Public Satisfaction Index (Indeks Kepuasan Masyarakat/IKM) method. This study used a quantitative descriptive approach. Data analysis techniques using the Public Satisfaction Index (IKM) approach, were calculated based on the weighted average value of each service element developed in the Regulation of Minister of State Aparatus and Bureaucratic Reform Number 16/2014. The findings of this study were that in general the assessment of public satisfaction index for Face to Face Tutorial held by UT Regional Office in Bengkulu obtained a Good Service criteria, with a Public Satisfaction Index value of 3.25 or converted to 81.16. It meant that the service performance was categorized as B (Good). Through continuous improvement, it was expected that the value of the Public Satisfaction Index (IKM) for Face-to-Face Tutorial services at UT’s Regional Office in Bengkulu can be maintained or improved in the following years.